Analisis Tekno-Ekonomi Pengaruh Suhu Curing terhadap Performa Mekanik Komposit Sandwich Carbon Fiber/PVC Foam: Tinjauan Sistematis dan Perspektif Efisiensi Biaya - Arya Syahputra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
Abstract This study presents a Systematic Literature Review (SLR) that integrates techno-economic analysis of curing temperature variations on the mechanical properties and failure behavior of carbon fiber sandwich composites with polyvinyl chloride (PVC) foam cores. The systematic review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol with structured searches across the Scopus, Web of Science, and Google Scholar databases, using keyword combinations: